Synthesis and Antiinflammatory Activity of Some Analogues of 4-Substituted-2-phenyl imidazolin-5(4H)-one Derivatives - Saravanan, V.S.; Vinoth Kumar, S.P.; De, Biplab; Kumar Gupta, Jayanta (Asian Journal of Chemistry, 2016)
A series of imidazolinone derivatives were synthesized from the respective oxazolinones followed by treatment with benzaldehyde to form their Schiff bases. The chemical structures of such seven synthesized compounds were confirmed by spectral analysis. The synthesized compounds on screening for antiinflammatory activity exhibited significant activity.